Aesthetic and psychosocial impact of dentofacial appearance after primary rhinoplasty for cleft lip and palate. Issue 10 (October 2021) - Dissaux, Caroline; Diop, Valérie; Wagner, Delphine; Talmant, Jean-Claude; Morand, Béatrice; Bruant-Rodier, Catherine; Ruffenach, Laeticia; Grollemund, Bruno
Abstract: The primary aim of this study was to demonstrate whether primary rhinoplasty shows aesthetic and psychosocial advantages for children with a complete unilateral cleft lip and palate. The second aim was to determine the satisfaction levels concerning the dentofacial appearance. Group A corresponded to patients from a center specialised in primary cheilo-rhinoplasty with 20 years' experience and Group B to patients who did not benefit from primary rhinoplasty. Children and their parents filled in a custom-designed satisfaction questionnaire on dentofacial appearance and its psychosocial impact. The variables studied were the main criterion (the nose) and secondary criteria (the upper lip, the smile, the profile and the face as a whole). 56 families consented to be involved in the study. The children did not rate statistically differently their social relationships if they had primary rhinoplasty or not. Parents however expressed very different views. They considered the nasal appearance of the children who had primary rhinoplasty as statistically more attractive and evaluated their psychosocial experience as significantly better. For the other parts of the face, in both groups, satisfaction levels of dentofacial appearance and psychosocial comfort were good (scores above 80/100). Yet, 44% of the families would go for further interventions, especially concerning the nose (13% of whom were in Group A and 42% in Group B). Within the limitations of this study, primary rhinoplasty seems to improve the patient's well-being and social life and, therefore, should be considered whenever appropriate.